Do liquidity or credit effects explain the behavior of the BKBM-LIBOR differential? - Poskitt, Russell; Waller, B. (Elsevier BV, 2011)
This paper examines the evolution of the relationship between the onshore and offshore benchmarks for New Zealand dollar funding during the global financial crisis. In August 2007 the BKBM-LIBOR differential switched from positive to negative and then widened considerably following the collapse of Lehman Brothers in September 2008, before narrowing gradually as the turmoil in financial markets subsided. Our structural regression model and decomposition analyses show that changes in liquidity, proxied by bid/ask spreads, largely explain the changes in the BKBM-LIBOR differential over this period and that credit risk factors only played a minor role. However our analysis also shows that bid/ask spreads in the offshore market price information regarding counterparty credit risk, suggesting that our initial results could understate the role played by credit risk factors.